La première occupation militaire romaine de Strasbourg (Bas-Rhin) - Stéphane Martin (Gallia)
On the basis of recent research on the Upper Rhine (Vindonissa, Oedenburg), this study focuses on dating and characterization of the first Roman establishment at Strasbourg, dated until recently from 12 B.C. From the few well defined layers uncovered during the recent excavations, this paper provides an update of the structures previously discovered and reviews the early findings (coinage, Italic Samian, amphorae). From the varied analyses the formation of the site, which seems to be confined in the third northwestern part of the present old town, can be dated to the first years of Tiberius’s reign, probably around 14-16 A.D. In the present state of data, the idea of an Augustan occupation has to be abandoned. There is some evidence of a military occupation so we could consider an identification with the quartering of the second legion, maybe altogether with an auxiliary unit.